Vision, Perception, and Attention through the Lens of Microsaccades: Mechanisms and Implications - Hafed, Ziad M.; Chen, Chih-Yang; Tian, Xiaoguang (Frontiers in Systems Neuroscience, 2015)
Microsaccades are small saccades. Neurophysiologically, microsaccades are generated using similar brainstem mechanisms as larger saccades. This suggests that peri-saccadic changes in vision that accompany large saccades might also be expected to accompany microsaccades. In this review, we highlight recent evidence demonstrating this. Microsaccades are not only associated with suppressed visual sensitivity and perception, as in the phenomenon of saccadic suppression, but they are also associated with distorted spatial representations, as in the phenomenon of saccadic compression, and pre-movement response gain enhancement, as in the phenomenon of pre-saccadic attention. Surprisingly, the impacts of peri-microsaccadic changes in vision are far reaching, both in time relative to movement onset as well as spatial extent relative to movement size. Periods of 100 ms before and 100 ms after microsaccades exhibit significant changes in neuronal activity and behavior, and this happens at eccentricities much larger than the eccentricities targeted by the microsaccades themselves. Because microsaccades occur during experiments enforcing fixation, these effects create a need to consider the impacts of microsaccades when interpreting a variety of experiments on vision, perception, and cognition using awake, behaving subjects. The clearest example of this idea to date has been on the links between microsaccades and covert visual attention. Recent results have demonstrated that peri-microsaccadic changes in vision play a significant role in both neuronal and behavioral signatures of covert visual attention, so much so that in at least some attentional cueing paradigms, there is very tight synchrony between microsaccades and the emergence of attentional effects. Just like large saccades, microsaccades are genuine motor outputs, and their impacts can be substantial even during perceptual and cognitive experiments not concerned with overt motor generation per se.